Small ruminant production in the West African humid zones - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
The Projet de Developpement de Petit Elevage dans la Kara (PRODEPEKA) is considered to be one of the best and most successful examples of an FAO/ National Government project (in this case the Republic of Togo), ever to have been undertaken. Located...